Situating Islamic Values in English Language Teaching: Documenting the Best Practices in Indonesia - Yoki Irawan (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2020)
Studies on the integration of moral, cultural, and religious values in language learning have recently increased. This is characterized by the number of these research topics. Indonesia as the world's largest Muslim-majority country must play a role in integrating Islamic values into learning, especially in learning English as a foreign language. However, in practice, there are many problems especially not all experts agree if topics related to religion are discussed in language learning. This article aims to discuss comprehensively the urgency and strategies in integrating Islamic values in English language learning in Indonesia. In general, the integration of Islamic values in language learning can be done through the integration of content and topics into the curriculum, teaching materials, and learning activities. Through the implementation of this, it is expected that students will be aware of the Islamic values in their daily lives in society to filter out irrelevant cultures and at the same time be able to acquire foreign language skills properly.